2022
DOI: 10.1128/aem.00486-22
|View full text |Cite
|
Sign up to set email alerts
|

Nonsynonymous Mutations in fepR Are Associated with Adaptation of Listeria monocytogenes and Other Listeria spp. to Low Concentrations of Benzalkonium Chloride but Do Not Increase Survival of L. monocytogenes and Other Listeria spp. after Exposure to Benzalkonium Chloride Concentrations Recommended for Use in Food Processing Environments

Abstract: Listeria monocytogenes tolerance to quaternary ammonium compounds has been raised as a concern with regard to L. monocytogenes persistence in food processing environments, including in fresh produce packing and processing environments. Persistence of L. monocytogenes can increase the risk of product contamination, food recalls, and foodborne illness outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
(73 reference statements)
3
6
0
Order By: Relevance
“…Strains that carried a mutation in fepR, as well as strains that artificially overexpress the efflux pump FepA exhibited increased tolerance not only towards BAC, but also towards CTAB, ciprofloxacin and gentamycin, indicating that extrusion by the transporter is rather unspecific. This observation further supports the previous hypothesis that de-repression of fepA is the reason for the observed QAC tolerance (Guérin et al 2014;Bland et al 2022;Bolten et al 2022;Douarre et al 2022). We further substantiated this hypothesis by showing that a mutation in the DNA binding domain of FepR resulted in decreased binding to the promoter of the fepRA operon in comparison to the wildtype FepR protein.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Strains that carried a mutation in fepR, as well as strains that artificially overexpress the efflux pump FepA exhibited increased tolerance not only towards BAC, but also towards CTAB, ciprofloxacin and gentamycin, indicating that extrusion by the transporter is rather unspecific. This observation further supports the previous hypothesis that de-repression of fepA is the reason for the observed QAC tolerance (Guérin et al 2014;Bland et al 2022;Bolten et al 2022;Douarre et al 2022). We further substantiated this hypothesis by showing that a mutation in the DNA binding domain of FepR resulted in decreased binding to the promoter of the fepRA operon in comparison to the wildtype FepR protein.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in accordance with previous studies, which focussed on serial adapted isolated L. monocytogenes and Listeria spp. strains that were exposed to BAC or ciprofloxacin stress and likewise found that the majority of strains acquired mutations in fepR (Bland et al 2022;Bolten et al 2022;Douarre et al 2022). FepR is a TetR-like transcriptional regulator that negatively regulates the fepRA operon, which encodes the regulator itself as well as the MATE family efflux pump FepA (Guérin et al 2014).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, we identified bcrABC , a plasmid-borne gene cassette which can confer tolerance of Listeria to low-levels of quats (Bolten et al, 2022), in 67/303 (22%) Listeria isolates. Previous studies surveying meat and vegetable processing plants (Hurley et al, 2019) and meat and salmon processing plants (Fagerlund et al, 2022) showed similar prevalence of bcrABC among Listeria populations.…”
Section: Discussionmentioning
confidence: 99%
“…In another study it was observed that two L. ivanovii strains isolated from postharvest sources in fresh produce processing could adapt to levels of benzalkonium chloride 3-fold higher than non-adapted wild types for the arising of nonsense mutations in the fepR regulator gene of the fepRA operon, which encodes the efflux pump FepA [35].…”
Section: Ivanovii Persistence and Tolerance To Harsh Conditionsmentioning
confidence: 99%